EFEKTIVITAS ORGANISASI BADAN PROMOSI PARIWISATA KOTA SEMARANG (BP2KS) - Annada Farhat Arifin; Tri Yuniningsih (Journal of Public Policy and Management Review, 2019)
Tourism is a strategic sector in economic development in Indonesia. Most province have a lot potential in tourism. Semarang city is a capital city of Central Java that have a lot potential and tourism attraction. To assist tourism development program dan to increase Semarang City’s competitiviness, local government formed a Tourism Promotion Board of Semarang City (BP2KS). This study attemps to describe and to analyse the organizational effectiveness of Tourism Promotion Board of Semarang (BP2KS) and to identify the determinat factors of Tourism Promotion Board of Semarang City’s effectiveness. This research uses qualitative approach with descriptive methode. This research uses goals optimization mode from Steers based on BP2KS’s duties according to the Mayor of Semarang Regulation Number 2 Year 2012. The result showed that the organizational effectiveness of BP2KS was not yet effective because the goals achievment based on the duties of BP2KS wasn’t the best. The determinant factors of BP2KS’s effectiveness pointed to negative or became the obstacle was from decentralisation, the size of organization, external and internal environment, role clarity, inovation and organizational adaptation, work plan making, communication, as well as search and utilization of resources . Advice that provided for improving the effectiveness of BP2KS is needed to make a tools for promotion (ex : website and application) and needed to do organizational reinforcement and improving the member’s activity in getting duties done based on the goals according to the Mayor of Semarang Regulation Number 2 Year 2012